The role of digital media in the 2011 Egyptian revolution. Issue 5 (3rd July 2020) - Hamanaka, Shingo
ABSTRACT: The Egyptian uprising in January 2011, widely known as the 25 January Revolution, was initially claimed to have been caused by the internet. However, the relationship between social media and participation in the anti-regime demonstrations is contested and opaque. This article explores this relationship through both a theoretical and empirical approach. More concretely, by using two survey data sets, we examine a hypothesis derived from a diffusion model of information and social movement theory. The two key findings are: (1) vanguards of the demonstrations were more active on social media than followers during the revolution, and (2) active bloggers tended to participate in demonstrations against the Mubarak regime. These findings contradict previous findings of social media's limited effect and indicate that social media diminishes the collective action problem in anti-government protests. They also indicate that the concept of political opportunity structure is useful for understanding the revolution.